Trust building in a multi-stakeholder forum in Jambi, Indonesia - Liswanti, N.; Tamara, A.; Arwida, S. (Routledge, 2023)
Liswanti et al. begin with a literature review on the role of trust in multi-stakeholder forums (MSFs) – something widely considered important. They use the work of Stern and Baird, which identifies four bases of trust: (1) dispositional (based on personal traits, hearsay), (2) rational (based on expectation of outcomes resulting from action), (3) affinitive (based on feelings of shared values or connectedness), and (4) system-based (due to fair and transparent procedures). The authors briefly describe the site, the MSF, and their methods. They use Q-methodology, which involves asking respondents to express their agreement or disagreement with a series of locally developed value statements, relating to the MSF. The authors analyze these responses as to the ways they indicate trust and approval (or lack thereof) regarding the MSF. Although MSF functioning was not without challenges, this analysis attributes its impressive and long-lasting successes to its members’ effective cooperation, excellent and relatively unbiased facilitation, and a shared vision – all contributing to the growth of trust within the group.